UTILIZATION OF LMS EL NINO FOR ENHANCING LANGUAGE LEARNING QUALITY IN THE ACCOUNTING DEPARTMENT POST-COVID-19 AT POLINES - Raharjo, Suko Suko; Hartono, Toni; Hamida, Nurul; Hendrawanto, Yusuf (Universitas 17 Agustus 1945 Semarang, 2024)
The COVID-19 pandemic has accelerated the adoption of Learning Management Systems (LMS) in educational institutions, highlighting their potential and challenges. This study examines the utilization of LMS EL Nino to enhance language learning quality in the Accounting Department at Politeknik Negeri Semarang (POLINES) post-pandemic. Using a descriptive qualitative approach, data were collected through in-depth interviews and participant observations from 168 students and 5 instructors. Thematic analysis identified key challenges, including technical issues (80%), lack of interaction (70%), and academic dishonesty concerns (60%). Significant opportunities were also found, such as flexible learning schedules (90%), access to diverse resources (85%), and self-paced learning (80%). Students generally viewed LMS EL Nino positively, appreciating its convenience and structured platform. Addressing the identified challenges and leveraging the opportunities can optimize LMS EL Nino for improved language education in the post-pandemic era. Keywords: LMS EL Nino, challenges, Opportunity, Language Learning